The Advantage of Arabic Language in Understanding of Quranis Issues | أهمية اللغة العربية في القضايا القرآنية - Nur Faizin Muhith (Al-Zahra : Journal for Islamic and Arabic Studies, 2010)
Arabic language has played an important role for understanding andovercoming linguistic issues of the Quran. This roles can be identified throughmainly the following issues; a command to memorize Qur’an, the miraculous of Qur’anic language, Arabic language competence as a requirement for theMufassir and understanding of Arabic language for translating the Quran. Themethod of the research is descriptive and analytical methods and the writerrefers to both classical and contemporary books that based on critical reading.